2020
DOI: 10.1093/neuonc/noaa044
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state fMRI detects alterations in whole brain connectivity related to tumor biology in glioma patients

Abstract: Background Systemic infiltration of the brain by tumor cells is a hallmark of glioma pathogenesis which may cause disturbances in functional connectivity. We hypothesized that aggressive high-grade tumors cause more damage to functional connectivity than low-grade tumors. Methods We designed an imaging tool based on resting-state functional (f)MRI to individually quantify abnormality of functional connectivity and tested it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 39 publications
8
83
0
Order By: Relevance
“…Even though the exact mechanisms remain speculative, such a global impact might be due to forward-propagation of locally perturbed connections within one network (such as tumour-associated destruction and oedema) to hierarchically connected further networks. Of note, the global impact we observe is in line with recent work that also included tumour-bearing voxels in their analysis 15 . Our results corroborate recent studies which observed a shift in connectivity profiles in patients with newly diagnosed glioma 23 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Even though the exact mechanisms remain speculative, such a global impact might be due to forward-propagation of locally perturbed connections within one network (such as tumour-associated destruction and oedema) to hierarchically connected further networks. Of note, the global impact we observe is in line with recent work that also included tumour-bearing voxels in their analysis 15 . Our results corroborate recent studies which observed a shift in connectivity profiles in patients with newly diagnosed glioma 23 .…”
Section: Discussionsupporting
confidence: 89%
“…We found patterns of network alterations across all patients irrespective of tumour size or location. In all cases, focal lesions were associated with widespread and symmetric anomaly in both hemispheres in a network-specific manner across all seven resting-state networks in line with recent work 15 , 23 . In our study, network anomaly refers to the relative deviation from network connectivity of a control population and does not necessarily reflect increased or decreased activity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We applied 0.2 threshold to the FA skeleton to account for cerebrospinal fluid partial volume effects ( Smith et al , 2006 ) and possibly oedema-related partial volume effects. The FA decreases may represent changes in global connectivity from the disease ( Stoecklein et al , 2020 ) or local WM integrity from injury during tumour resection. Myelin sheets and axonal membranes restrict diffusion perpendicular to their axis, hence isotropic water diffusion (lower FA values) could reflect decreased axonal membrane integrity ( Beaulieu, 2002 ); potentially exacerbated by surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, it has become clear that brain networks and their alterations associated with GBM have an impact on survival. Stoecklein et al demonstrated that resting-state functional connectivity (rsFC) measured by MRI is affected by gliomas throughout the whole brain and this information indicated individual glioma disease burden ( 17 ). Daniel et al took these findings further to show that functionally connected voxels can be routinely found within glioblastoma tumors and that intra-tumor connectivity strength is a prognostic marker for overall survival ( 18 ).…”
Section: Introductionmentioning
confidence: 99%